Penguatan Kesiapan Berperilaku Ramah Lingkungan Siswa SMA melalui Pengembangan Pedagogi Spesifik Berbasis PjBL pada Mata Pelajaran Ekologi - Zayyana Fatati Azizah; Puguh Karyanto; Baskoro Adi Prayitno; Raden Rara Sapartini (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2017)
This research aims to know strengthening readiness of high school students friendly environment behavior through specific pedagogy based PjBL development on ecological subject. This research is a research and development refers to Thiagarajan 4-D models which is modified into 3-D models without doing disseminate stage. The development sample includes an expert appraisal sample of 4 validators and 1 educational practitioner, a developmental testing sample of 8 students and 1 biology teacher, an initial data collection sample of 54 students, and a field testing sample of 34 students and 1 biology teacher. Data collection instruments used knowledge, NEP (attitude), and concern questionnaire for needs analysis, expert appraisal, and student's responses to module and LKS; Observation sheets for target-population analysis and syntax implementation; Interviews for needs analysis, students' responses to environmental learning on field testing; And learning device documentation for needs analysis. Initial data collection and field testing used purposive sampling. The validity test addressed to knowledge questionnaire and SSP based PjBL preliminary product. The data analysis by processing students knowledge, NEP, and concern questionnaire used independent sample t test with SPSS 21. The results of research showed that the data of knowledge, attitude, and concern were strengthened and there was no correlation between the data on initial data collection and final research (knowledge sig. 0,045; attitude sig. 0,000; concern sig. 0,000). Based on the result of the research, concluded that readiness of high school students friendly environment behavior strengthened through specific pedagogy based PjBL development on ecological subject.